Simultaneous analyte indicator binding assay (SBA) for the monitoring of reversible host–guest complexation kinetics. Issue 94 (14th November 2021) - Miskolczy, Zsombor; Megyesi, Mónika; Sinn, Stephan; Biedermann, Frank; Biczók, László
Abstract : Competitive binding of an indicator dye and an optically silent guest was exploited to develop a powerful method for the accurate determination of the kinetic and thermodynamic parameters of host–guest complex formation. Abstract : Very little information is available on the kinetics of the self-assembly and dissociation of optically silent building blocks despite the importance of such data in the rational design of tailor-made host–guest systems. We introduce here a novel time-resolved method that enables the simultaneous determination of complex formation and complex dissociation rate constants for inclusion-type host–guest complexes. The simultaneous analyte indicator binding assay (SBA) gives also direct access to binding affinities, thus largely simplifying the experimental procedure for a full kinetic and thermodynamic characterisation of host–guest systems.